Comparison of Hybrid Control Schemes for Vibration Suppression of Flexible Robot Manipulator - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli; Ahmad Nor Kasruddin, Nasir (2009)
This paper presents a comparative assessment of control schemes for vibration suppression and end-point trajectory tracking of a flexible robot manipulator. A constrained planar single-link flexible robot manipulator is considered and the dynamic model of the system is derived using the assumed mode method. To study the effectiveness of the controllers, initially a collocated PD controller is developed for control of rigid body motion. This is then extended to incorporate a non-collocated PID controller and a feedforward controller based on input shaping techniques for control of vibration (flexible motion) of the system. For input shaping controller, the positive input shapers with different derivatives are proposed and designed based on the properties of the system. Simulation results of the response of the manipulator with the controllers are presented in time and frequency domains. The performances of the control schemes are assessed in terms of level of vibration reduction, input tracking capability and speed of response. Finally, a comparative assessment of the control techniques is presented and discussed.